2001
DOI: 10.1063/1.1359149
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of amorphous germanium in an Al/a-Ge bilayer film deposited on a SiO2 substrate

Abstract: The crystallization of amorphous Ge(a-Ge) in an Al (134 nm) and a-Ge (108 nm) thin-film bilayer deposited on a SiO2 substrate has been examined by a cross section transmission electron microscope technique. When crystallization of a-Ge begins at 125 °C, amorphous AlGe (a-AlGe) alloy is formed in the Ge layer. Then, the a-AlGe alloy layer also appeared at the surface of the bilayer. After complete crystallization, those amorphous layers disappeared and the bilayer film has been converted to a polycrystalline fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…28,29) Anomalous metal-mediated crystallizations by low temperature annealing were also observed in amorphous semiconductor/metal double-layered films, and ascribed to very fast grain boundary diffusion of Si (or Ge) atoms through metal layers. 30,31) Since both Fe and Si diffusivities are small and their values for Fe are much smaller than that for Si in the bulk B20-type ordered FeSi alloy, 32) the insufficient annealing procedures (the short period and low temperature) may hinder the growth of the ordered FeSi and FeSi 2 phases in the present Fe/Si hybrid clusters.…”
Section: Discussionmentioning
confidence: 99%
“…28,29) Anomalous metal-mediated crystallizations by low temperature annealing were also observed in amorphous semiconductor/metal double-layered films, and ascribed to very fast grain boundary diffusion of Si (or Ge) atoms through metal layers. 30,31) Since both Fe and Si diffusivities are small and their values for Fe are much smaller than that for Si in the bulk B20-type ordered FeSi alloy, 32) the insufficient annealing procedures (the short period and low temperature) may hinder the growth of the ordered FeSi and FeSi 2 phases in the present Fe/Si hybrid clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the difference has been discussed in terms of film thickness 21,22 and impurities. 19,23 The present study revealed that crystallization temperature of a-Ge films, of the fixed thickness of 40 nm, varies from 500 • C to 600 • C depending on thermal history, with corresponding variations in the amorphous structure and the crystallization behavior from coarse particles with a hexagonal structure to homogeneous nanograins of the diamond cubic structure.…”
Section: Crystallization Dynamicsmentioning
confidence: 99%
“…The values reported in the literature are grouped into two: low-temperature and high-temperature crystallization that occur at 400-500 • C [17][18][19] and at 600-650 • C, 20 respectively. The origin of the difference has been discussed in terms of film thickness 21,22 and impurities.…”
Section: Crystallization Dynamicsmentioning
confidence: 99%
“…5,6 Metal-induced crystallization (MIC) may occur in hermetic films during MEMS packaging. [7][8][9][10] In MIC, metal induces crystallization of semiconductor at a low temperature. The driving force for MIC is the difference between the free energies of the crystallized phase and the amorphous phase.…”
Section: Introductionmentioning
confidence: 99%